Information and communication on technology for the fight against global warming first international conference, ICT-GLOW 2011, Toulouse, France, August 30-31, 2011, proceedings - Kranzlmüller, Dieter; Toja, A Min (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the First International Conference on Information and Communication Technology for the Fight against Global Warming, ICT-Glow 2011, held in Toulouse, France in August 2011. The 16 revised papers presented were carefully reviewed and selected from 24 submissions. They address the following topics: parallel computing, ICT for transportation, cloud and pervasive computing, measurement and control and storage.